Obesity and outcomes in patients treated with chemoradiotherapy for esophageal carcinoma. Issue 2 (26th April 2013) - Wang, J.; Myles, B.; Wei, C.; Chang, J. Y.; Hofstetter, W. L.; Ajani, J. A.; Swisher, S. G.; Cox, J. D.; Komaki, R.; Liao, Z.; Lin, S. H.
Summary Body mass index (BMI) is a risk factor for comorbid illnesses and cancer development. It was hypothesized that obesity status affects disease outcomes and treatment‐related toxicities in esophageal cancer patients treated with chemoradiotherapy (CRT). From March 2002 to April 2010, 405 patients with non‐metastatic esophageal carcinoma at MD Anderson Cancer Center treated with either definitive or neoadjuvant CRT were retrospectively analyzed. Patients were categorized as either obese (BMI ≥ 25 kg/m2) or nonobese (BMI < 25 kg/m2). Progression‐free survival and overall survival times were examined using the Kaplan–Meier method and Cox proportional hazards regression analysis. One hundred fifteen (28.4%) patients were classified as nonobese and 290 (71.6%) as obese. Obese patients were more likely than others to have several comorbid diseases (P < 0.001), adenocarcinoma located distally (P < 0.001), and have undergone surgery (P = 0.004). Obesity was not associated with either worse operative morbidity/mortality (P > 0.05) or worse positron emission tomography tumor response (P = 0.46) on univariate analysis, nor with worse pathologic complete response (P = 0.98) on multivariate analysis. There was also no difference in overall survival, locoregional control, or metastasis‐free survival between obese and nonobese patients (P = 0.86). However, higher BMI was associated with reduced risk of chemoradiation‐induced high‐grade esophagitis (P = 0.021), esophageal stricture (P < 0.001), and high‐grade hematologic toxicity (P < 0.001). In esophageal cancer patients treated with CRT, obesity is not predictive of poorer disease outcomes or operative morbidities; instead, data suggest it may be associated with decreased risk of acute chemotherapy‐ and radiotherapy‐related treatment toxicities.